Identification of rare and common regulatory variants in pluripotent cells using population-scale transcriptomics - Bonder, Marc Jan; Smail, Craig; Gloudemans, Michael J.; Frésard, Laure; Jakubosky, David; D’Antonio, Matteo; Li, Xin; Ferraro, Nicole M.; Carcamo-Orive, Ivan; Mirauta, Bogdan; Seaton, Daniel D.; Cai, Na; et al. (Nature genetics, 2021)
Induced pluripotent stem cells (iPSCs) are an established cellular system to study the impact of genetic variants in derived cell types and developmental contexts. However, in their pluripotent state, the disease impact of genetic variants is less well known. Here, we integrate data from 1,367 human iPSC lines to comprehensively map common and rare regulatory variants in human pluripotent cells. Using this population-scale resource, we report hundreds of new colocalization events for human traits specific to iPSCs, and find increased power to identify rare regulatory variants compared with somatic tissues. Finally, we demonstrate how iPSCs enable the identification of causal genes for rare diseases. Integrative data analysis of 1,367 human iPSC lines maps common and rare regulatory variants that colocalize with loci associated with human traits and diseases.